Peptide Self-Assembly Is Linked to Antibacterial, but Not Antifungal, Activity of Histatin 5 Derivatives - Lee Schnaider (American Society for Microbiology, 2020)
ABSTRACT The rise of multidrug-resistant pathogens has awakened interest in new drug candidates such as antimicrobial peptides and their derivatives. Recent work suggests that some antimicrobial peptides have the ability to self-assemble into ordered amyloid-like nanostructures which facilitate their antibacterial activity. Here, we evaluate a histatin-based antimicrobial peptide, and its self-assembling derivative, in the interplay between self-assembly, membrane interactions, and antibacterial and antifungal activities. We demonstrate substantial membrane targeting by both peptides, as well as mechanistic insights into this mode of action, which correlates to their antifungal activity and is not affected by their self-assembling state. The ability to self-assemble does, however, significantly affect peptide antibacterial activity against both Gram-negative and Gram-positive bacteria. These results are surprising and hint at important distinctions between antifungal and antibacterial peptide activities in prokaryotes and eukaryotic microbes. IMPORTANCE Antimicrobial peptides are important modulators of host defense against bacterial, fungal, and viral pathogens in humans and other multicellular organisms. Two converging paradigms point to a link between antimicrobial peptides that self-assemble into amyloid-like nanoassemblies and classical amyloidogenic peptides that often have potent broad-spectrum antimicrobial activity, suggesting that antimicrobial and amyloidogenic peptides may represent two sides of the same coin. Here, we asked if the ability of an antifungal peptide to self-assemble affects its antifungal or antibacterial activity. We found that modifications of classical antifungal peptide derivative allowed it to self-assemble and did not alter its antifungal activity, and yet self-assembly substantially increased the antibacterial activity of the peptide. These results support the idea that peptide self-assembly can enhance antibacterial activities and emphasize a distinction between the action of antifungal peptides and that of antibacterial peptides. Accordingly, we suggest that the possible generality of this distinction should be widely tested.